PENYULUHAN PROGRAM PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) MELALUI KEGIATAN MENCUCI TANGAN PAKAI SABUN PADA PENDIDIKAN ANAK USIA DINI - Ade Nurhasanah Amir; Honesty Diana Morika; Rikayoni Rikayoni (Stikes Syedza Saintika Padang, 2024)
Hands are the main medium for transmitting disease-causing germs due to the lack of hand washing habits. Children are the highest sufferers of diarrhea and respiratory diseases, which often lead to death. Soap has reached almost all households in Indonesia, but only about 3% use soap every year. On average, 100,000 children in Indonesia die from diarrhea. The child mortality rate in Indonesia reaches 32 per 1,000 live births. The death rate is almost 19% due to diarrhea. The behavior of the Indonesian people towards the 5 important times of washing hands with soap (CTPS) can be influenced by the level of knowledge. The goal is to increase knowledge and be able to demonstrate hand hygiene exercises on. The impact of the lack of knowledge and understanding of Clean and Healthy Behavior (PHBS) by washing hands is one of the factors causing the high spread of infectious diseases such as diarrhea, dengue, worms and others. The benefits of introducing PHBS from an early age will affect children's behavior, namely building awareness in children. The method used is to provide direct counseling and training to the general public and children in particular by learning to play while learning. The results obtained were that outreach and training activities went well and participants actively participated in extension and training activities to completion. Extension and training are carried out interactively between the resource persons and the training participants. The conclusion from community service activities can run well and smoothly. Participants are enthusiastic and can work together wellKeywords: Counseling, Demonstration, Hand Hygiene